RF-Induced Heating Estimation of a Stent in a 3T MRI Using Transfer Function Approach With a Tabletop E-Field Generator - Hongbae Jeong; Joshua W. Guag; Ananda Kumar (IEEE Access)
The use of a transfer function (TF) method enables a conservative estimation for radio frequency (RF) safety assessment of active implantable devices (AIMDs). The TF approach can be applied to various scan conditions, patient populations, and device trajectories inside the human body, reducing the computational burden of full-wave electromagnetic (EM) simulation. The in vitro TF model validation process is time-consuming, requiring tests in various sample trajectories that collectively exceed eight hours. Here, we demonstrated reducing the burden of the TF approach using a low-power tabletop E-field generator. We measured the TF of the stent via the piecewise excitation method at 128 MHz and validated it by exposing the device under diverse test exposure fields using a tabletop E-field generator that requires less phantom material, lower cost than whole-body coil or MRI scanner, and with reduced experimental safety hazards or shielded room requirements. The TF approach was used to predict radio frequency (RF)-induced power near the stent tip at 128 MHz and predicted values were then compared against measured values. We also used a body transmit coil to compare the conventional in vitro TF model validation approach and tabletop E-field generator. With the tabletop E-field generator, the equivalent absolute normalized error was ( $0.37~± ~0.31$ dB) compared to the body transmit coil tests ( $0.43~± ~0.15$ dB), and the required test time decreased from eight to three hours. In summary, we showed how a low-power compact E-field generator can be used for in vitro TF model validation with reduced testing time and cost without using a shielded room.